Accelerometer-Based Physical Activity, Sedentary Time, and BMI among Preschoolers in Puerto Rico - Ramírez-Marrero, Farah A.; Hernández-Torres, Emmanuel; Torres-Villela, Luis; Estrada-Oliver, Luis G.; Meléndez-Nieves, Anthony (Puerto Rico Health Sciences Journal, 2022)
Objective: A minimum of 3-h/day of any intensity physical activity (PA) has been recommended for preschoolers. No previous study has documented accelerometer-based PA and sedentary time (ST) among Hispanic preschoolers in Puerto Rico, a population with high obesity and low PA prevalence. The purpose of this study was to describe and compare total, weekdays (during- and out-of-preschool) and weekend PA and ST, and test associations with body mass index (BMI). Methods: A group of 3-5-year-old preschoolers (9 boys,13 girls) completed height and weight measurements, and wore an accelerometer during 7-days. Shapiro-Wilk, Mann-Whitney U test and Spearman correlations were used to test for normality, sex differences and associations, respectively. Results: No sex differences were observed for BMI, weekdays and weekends PA and ST. Light to vigorous intensity PA (LVPA=3.2±0.6 h/day) and moderate to vigorous intensity PA (MVPA=80.4±21.7 min/day) were within guidelines only on weekdays. LVPA occupied 21.3% (15.4±3.7 min/h), MVPA 9.5% (6.6±2.3 min/h), and ST 65.3% (4.8±0.4 h/day) of preschool time. Boys had higher MVPA than girls only during-preschool time. BMI indicative of overweight-obesity was identified in 36.3%, and BMI directly correlated with total ST and inversely correlated with LVPA. Conclusion: Total and during-preschool LVPA and ST, and their association with BMI highlight the need for interventions to promote PA and reduce ST, particularly during-preschool time.